(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article examines an examination of 16 patients aged 1 to 14 years with a laboratory confirmed (cerebrospinal fluid PCR) diagnosis of enterovirus meningitis. All patients, depending on age, were divided into 3 groups. The main group of cases was made up of school children. The course of the disease in all cases is benign with a short febrile period, a short period of clinically pronounced meningeal syndrom.